MAIN PSYCHOLOGICAL PROBLEMS OF STUDENTS' PROFESSIONAL DIRECTION IN MODERN SCHOOLS (American Journal of Interdisciplinary Research and Development, 2023)
This article theoretically analyzes the main psychological problems of career orientation of students in modern schools. The results of a number of researches related to the important tasks of professional education, stages of professional formation, career choice, career orientation, understanding and definition of professional identity are described.